Forward-angle neutron-proton scattering at 96 MeV - C. Johansson (2018)
The differential np scattering cross section has been measured at 96 MeV in the angular range θc.m. = 20°-76°. Together with an earlier data set at the same energy, covering the angles θc.m. = 74°-180°, a new data set has been formed in the angular range θc.m. = 20°-180°. This extended data set has been normalized to the experimental total np cross section, resulting in a renormalization of the earlier data of 0.7%, which is well within the reported normalization uncertainty for that experiment. A novel normalization technique has been investigated. The results on forward np scattering are in reasonable agreement with theory models and partial wave analyses and have been compared with data from the literature. ©2005 The American Physical Society.